2015
DOI: 10.1111/1753-0407.12276
|View full text |Cite
|
Sign up to set email alerts
|

Increased T cell immunoglobulin and mucin domain containing 4 (TIM‐4) is negatively correlated with serum concentrations of interleukin‐1β in type 2 diabetes

Abstract: The results of the present study indicate that TIM-4 contributes, at least in part, to the pathogenesis of T2D, possibly by regulating IL-1β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The level of Tim-4 mRNA expression in peripheral blood of patients with Type 2 diabetes mellitus was significantly increased and negatively correlated with LDL (94). The latest report found that blocking Tim-4 could aggravate atherosclerosis in ldlr −/− mice (95), and the expression of Tim-4 mRNA was increased in liver tissues of rats on a high fat diet (96).…”
Section: Chronic Metabolic Diseasementioning
confidence: 99%
“…The level of Tim-4 mRNA expression in peripheral blood of patients with Type 2 diabetes mellitus was significantly increased and negatively correlated with LDL (94). The latest report found that blocking Tim-4 could aggravate atherosclerosis in ldlr −/− mice (95), and the expression of Tim-4 mRNA was increased in liver tissues of rats on a high fat diet (96).…”
Section: Chronic Metabolic Diseasementioning
confidence: 99%
“…It has been stated that TIPE2 mRNA expression was substantially declined in individuals with SLE in contrast to healthy individuals and was negatively correlated with the SLE disease activity index (SLEDAI) and myxoma resistance protein 1 (MX1) mRNA expression levels in SLE participants [17]. Research by Feng Licon firmed that TIPE2 overexpression by adeno-associated virus prompted macrophage polarization to a M2 phenotype in vitro and in vivo in the SLE mouse model and substantially diminished SLE severity [9]. Xi et al stated that TIPE2 mRNA expression was substantially diminished in PBMCs from individuals with chronic hepatitis B in contrast to healthy people, and TIPE2 expression was negatively correlated with blood levels of ALT, AST, and total bilirubin (Tbil) and with HBV load in these patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers, including IL-1 β and TNF- α , are escalated in the serum and tissues of diabetics [8, 9], and TNF- α is a vital regulatory molecules of insulin resistance in T2DM; the neutralization of TNF- α might represent a strategy for combating obesity-induced insulin resistance in individuals with T2DM. In accordance with previous research, our study showed that the mRNA level of TIPE2 was negatively linked with TNF- α and IL-6 in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Moreover, we observed increased Tim-4 expression on PBMCs from systemic lupus erythematosus 22 and type 2 diabetes patients. 23 It therefore appears that the potential role of Tim-4 is to downregulate the innate immune system, particularly macrophages, in order to decrease excessive inflammatory reactions. Recently, we identify Tim-4 as a critical regulator of LPS-induced macrophage activation by inhibiting NO production in vitro.…”
Section: Discussionmentioning
confidence: 99%